Sistem Pendidikan Di Indonesia: (Antara Keinginan dan Realita) - Kukuh Wurdianto; Dewi Ratna Juwita; Yossita Wisman; Bernisa Bernisa (Jurnal Ilmiah Kanderang Tingang, 2024)
The educational system in Indonesia is based on the national education system. However, there is a gap between the ideals and the reality. This can be seen from many faktors such as the weakness in management sector, the low support from the government and the community, low learning effectivity and efficiency, educational resource inferiority, and the low standard of learning. As a result, the expectations of a good education system is still far from satisfaction. Many solutions have been proposed including updating the curriculum nationally, but still many serious constraints are faced. These circumstances then require systematic reformulation by considering many faktor namely the politic, economic, social and cultural aspects of Indonesia.